Influence of training years on upper-body strength and power changes during the competitive season for professional Australian rules football players - Hrysomallis, C.; Buttifant, D. (Journal of Science and Medicine in Sport, 2012)
To determine if upper-body strength or power changes during the competitive season for elite Australian rules footballers and what influence the number of training years has on any changes.